(untitled) (Jurnal Bahasa, 2006)
This article discusses the inter-connection between variables of phonology and social variables and phonological variations frequently used by urban community of Kuching, Sarawak. Six phonological variations focused are (al), (a2), (r), (h), (ai) and (au). The usage of the phonological variables is explored in four different types of Ianguage styles, namely word list, passage, interview, and casual, based on socio-economic status (SES), i.e. occupation, income, education, and housing indices. The study is based on sociological urban dialectology. This study reveals that the middle SES group is prone to experience phonological shift compared with the lower group. The shit is probably due to social context elements such as better economic status, work environment, education level and a wider scope of communication. Even though the lower group retains their phonological identity of the original Sarawak Malay dialect, it remains at a mediocre level. The result also shows that at present there is language integration, especially in pronunciation between the urban communities ofKuching with standard pronunciation in Peninsular Malaysia.